2014
DOI: 10.1016/j.amsu.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal degeneration and type Ib endoleak with proximal aneurysm rupture: A case report, review of literature and technical suggestions

Abstract: IntroductionDespite the reduction in mortality incidences of AAA in proportion to increased use of EVAR, the natural history of aneurysms with the presence of an endoleak post EVAR remains unclear. With a cumulative AAA rupture incidence of 2% at six years post EVAR, the lack of an immediate endoleak is not an indicator of success.Case reportWe present a case of an 80-year-old man who presented to the emergency department with generalised abdominal pain and hypotension. Four years earlier he had underwent an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Specific data on selected studies are reported in Table 1. [7][8][9][10][11][12][13][14][15][16][17] Patients and EVAR procedure Total number of included patients was 29. Patients' demographics are summarized in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Specific data on selected studies are reported in Table 1. [7][8][9][10][11][12][13][14][15][16][17] Patients and EVAR procedure Total number of included patients was 29. Patients' demographics are summarized in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…This is reflected in the lack of cross-clamping (short neck suprarenal and supraceliac), lack of ischemic time or long operative period, and, in worse-case scenarios, EVAR explantation. 9 , 10 ) Furthermore, the introduction of the new novel intraoperative assessment technique can maximize the benefits of the procedure by diminishing radiation exposure and/or contrast use.…”
Section: Discussionmentioning
confidence: 99%
“…Crucial for a favorable outcome and especially for the recovery of renal function is the drainage of the abdominal cavity and retroperitoneum (7,9).…”
Section: Discussionmentioning
confidence: 99%